Factors that influence in the capital structure of firms wich belong to the São Paulo Stock Exchange - Amado Tristão, Pâmela; Rabelo Dutra, Vanessa (Revista de Administração da UFSM, 2012)
http://dx.doi.org/10.5902/198346596279 The aim of this work is to study the influence of variables size, profitability, growth and tangibility in the capital structure of firms which belong to the São Paulo Stock Exchange (BOVESPA) in 2010. Concerning this, it was developed a descriptive and quantitative study. It was made a multiple regression using the size, profitability, growth and tangibility as independent variables and the level of indebtedness as dependent variable, based on the data from the firms’ financial demonstrative. It has been concluded that the independent variables show a significant influence in the level of indebtedness when analyzed together. Though, when analyzed separately the only one which has shown a considerable influence is the tangibility. The other variables size, profitability and growth did not show any sign of influence in the regression models. The results obtained corroborate for future studies analyzing different variables in the capital structure.